Strength, Deformation and Fragility assessment of Reinforced Concrete Moment Resisting frame designed by Force Based Design and the Performance Based Plastic Design method for Seismic loads. (February 2021) - Dalal, Sejal P.; Dalal, Purvang
Abstract: A 20 storied Reinforced Concrete (RC) Moment Resisting Frame (MRF) has been analysed and designed by Force Based Design (FBD) method and the Performance Based Plastic Design (PBPD) method. The PBPD frames were designed for all the three performance levels namely Immediate Occupancy, Life safety and Collapse Prevention of the basic safety objective. The guidelines of the Indian Standard codes along with established principles of design have been incorporated in the study. Nonlinear static pushover analysis was the tool used to evaluate the seismic performance of the frames in terms of strength and deformation. The fragility assessment has been carried out in terms of Spectral displacement obtained from the pushover analysis results for different specified damage states. Results indicate that PBPD method excels the FBD method, both in terms of seismic performance and fragility.